Effect of Polyvinyl Alcohol (PVA) Concentration and Stirring Time on The Mechanical Properties of Biodegradable Plastic from Kepok Banana Peel Starch - Doni, Monica Anatasya; Jonuarti, Riri; Wulan, Ratna; Jhora, Fadhila Ulfa (CIVED, 2023)
One solution is to use bioplastics, which can replace synthetic plastics that are difficult to decompose. Starch is one of the materials used in the manufacture of bioplastics because it is naturally degradable. However, bioplastics made from starch tend to be brittle and easily damaged, so additional materials are needed to overcome this problem. Polyvinyl alcohol (PVA) is one of the materials used in the manufacture of bioplastics because it has properties that can be degraded naturally, is non-toxic, and is able to form good quality plastic films. This study aims to examine the effect of PVA concentration and stirring time on the mechanical properties of biodegradable plastic derived from kepok banana peels. This study used a completely randomized design with three variations of PVA concentration (3%, 4%, and 5%) and three variations of stirring time (25 minutes, 35 minutes, and 45 minutes). The results showed that at a PVA concentration of 5% with a stirring time of 45 minutes, bioplastics showed the best quality with a tensile strength value of 2.25 MPa, the best elongation at break was 416%, and the best elasticity was 0.541. In biodegradation, all samples were completely degraded within 7 days. It can be included that the addition of PVA concentration and the length of stirring effecth the mechanical properties of bioplastics but not on the biodegradation test.